2015
DOI: 10.1016/j.neuropharm.2014.12.010
|View full text |Cite
|
Sign up to set email alerts
|

Two aspects of ASIC function: Synaptic plasticity and neuronal injury

Abstract: Extracellular brain pH fluctuates in both physiological and disease conditions. The main postsynaptic proton receptor is the acid-sensing ion channels (ASICs). During the past decade, much progress has been made on protons, ASICs, and neurological disease. This review summarizes the recent progress on synaptic role of protons and our current understanding of how ASICs contribute to various types of neuronal injury in the brain.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
57
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(59 citation statements)
references
References 103 publications
2
57
0
Order By: Relevance
“…Overall, data here presented further confirm that ASICs can mediate proton signaling at synaptic sites [52] and reveal for the first time alink between ASIC1a channels and mGlu receptors. Of note, recent evidence published by Gan and colleagues [19] demonstrated a crosstalk between group I mGlu receptor and ASIC3 in dorsal root ganglion (DRG) neurons.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…Overall, data here presented further confirm that ASICs can mediate proton signaling at synaptic sites [52] and reveal for the first time alink between ASIC1a channels and mGlu receptors. Of note, recent evidence published by Gan and colleagues [19] demonstrated a crosstalk between group I mGlu receptor and ASIC3 in dorsal root ganglion (DRG) neurons.…”
Section: Discussionsupporting
confidence: 80%
“…On the one hand, this study highlights a novel role of ASICs in hippocampal synaptic plasticity and in cellular responses to mGlu receptors activation, opening a stream of investigation on their possible role in regulating cognitive processes; on the other it might shed new light on the possible contribution of these channels to pathological events at the synapse. Accordingly, several reports have previously shown the involvement of ASICs in ischemic neuronal injury, traumatic neuronal multiple sclerosis and Parkinson's disease [52]. Therefore, ASICs are emerging as potential therapeutic targets for the treatment of several brain disorders [53].…”
Section: Discussionmentioning
confidence: 99%
“…Synaptic transmission reduces pH at the synaptic cleft, and this acidification contributes to postsynaptic currents and synaptic plasticity (1)(2)(3)(4). Moreover, acidosis is common in neurologic diseases and is a major cause of neuronal injury in diseases, such as ischemia (5,6). These observations indicate that proton-mediated signaling is important for both physiologic and pathophysiological responses.…”
mentioning
confidence: 99%
“…The ASIC subunits expressed throughout mouse brain are ASIC1a, -2a, and -2b (8). Electrophysiological studies further showed that ASIC1a and ASIC2 subunits are the main contributor to acidactivated currents in the vast majority of brain neurons (5). ASIC1a is the key determinant of the acid-activated current, whereas ASIC2 plays important modulator roles.…”
mentioning
confidence: 99%
“…The review covers a range of topics from the history of the first electrophysiological observations of these channels (Krishtal et al, 2015) to what we currently know of their structure and biophysical properties (Gründer and Pusch, 2015), their pharmacology (Baron and Lingueglia, 2015), some of the mechanisms by which they are regulated (and especially those by neuropeptides, Vick and Askwith, 2015) and their physiological roles in both the central and the peripheral nervous systems. Brain ASICs have been implicated in functions such as synaptic plasticity and neuronal injury (Huang et al, 2015), but the largest body of data to-date has been obtained on their contribution to sensory function in the peripheral and/or the central nervous systems. This includes nociception, with roles for ASIC channels in pain (Deval and Lingueglia, 2015;Sluka and Gregory, 2015) and migraine (Dussor, 2015), as well as in gastrointestinal function (Holzer, 2015), mechanoreception (Omerbasic at al.…”
mentioning
confidence: 99%